Sediment sink-source transitions in the middle and lower reaches of the Yangtze River estuary - Yang, Yunping; Zheng, Jinhai; Zhang, Mingjin; Zhu, Lingling (Frontiers in Marine Science, 2023)
Human activities have severely altered the Yangtze River (Changjiang) Estuary’s pattern, beach-trough shape, and delta in recent decades. Existing research has studied the sediment “source–sink” relationship between the Yangtze River mainstream and estuary using gauged suspended sediment data. This method overestimated the decline in the suspended sediment concentration in the estuary, as riverbed scouring or deposition have not filtered out amounts related to sand mining or waterway dredging. This study took the Yangtze River Basin as the research subject and used spot observed runoff, sediment, and riverbed topography data gathered between 1980 and 2020 to analyze the sediment trapping effect of the Three Gorges Reservoir (TGR) and study the “source-sink” relationship of suspended sediment transport in the middle-lower reaches of the Yangtze River. The Yangtze Estuary Delta is dominated by scouring, which shows an increasing trend. During the operation of the TGR (2003–2020), the suspended sediment load entering the Yangtze Estuary from the Yangtze River mainstream decreased by 68% compared to the amount prior to operation commencing (1960–2002). However, studies have found that there are still large amounts of bottom sand with riverbed load movement characteristics after the operation of the Three Gorges Project and that riverbed souring of the downstream dam has increased the degree of deposition recharge. The amount of sediment in the Yangtze Estuary decreased between 2003 and 2018 compared with the period 1981 to 2002, with an annual decrease of 16.9%. The cumulative deposition of the Yichang–Datong and Datong–Xuliujing reaches from 1981–2002 was 3.13×10 8 m 3 and 1.60×10 8 m 3 , respectively, and cumulative scouring from 2002–2018 was 28.52×10 8 m 3 and 16.01×10 8 m 3 . This study concluded that even if the suspended sediment load entering the estuary decreased significantly after the operation of the TGR, the riverbed in the middle-lower reaches of the Yangtze River has gradually transformed from the “sink” of sediment deposition to the “source” of sediment supply.